The role of technical knowledge in determining patterns of financial behavior: A field study of a sample of investors in foreign exchange markets in less - Noori Dawda, Ranj Mohammed; Sulaiman, Shaima Amin (Journal of University of Human Development, 2016)
The research dealt with a contemporary topics in the financial field, the financial knowledge is a strategic asset to individual, who can rely upon and exploited for financial gains to ensure financial success in generating wealth and entrepreneurial him and the community, the basic idea for this study is focused on strengthening the financial behaviors of the individual through the knowledge based on technical analysis, which is one of the elements that ensure the correct trading in the foreign exchange markets. The study aimed to investigate the impact of technical knowledge on patterns of financial behavior, the study population are investors in the foreign exchange markets in the Kurdistan Region of Iraq that has been selected as random sample of the study, the questionnaire have been formed based on previous studies and that was the main tool to collect field data, and adopted (59) of the valid forms of origin (80) distributed form on individuals traders in those markets. The most important results of the study reached there is significant effect relationship of technical knowledge on financial behavior, the study concluded that there is the need to study the literature by researchers, and take advantage of the relationship between technical knowledge and financial behavior model.